Comparison of Success Rate in Complete Supine Versus Semi Supine Percutaneous Nephrolithotomy: (The first pilot study in randomized clinical trial) - Falahatkar, Siavash; Ghasemi, Ali; Gholamjani Moghaddam, Keivan; Esmaeili, Samaneh; Kazemnezhad, Ehsan; Seyed Esmaeili, Seyed Naser; Motiee, Reza (Urology Journal, 2017)
Purpose: To compare outcomes and complications of percutaneous nephrolithotomy (PCNL) in the complete supine versus semi supine position in order to select the best position. Materials and Methods: In this clinical trial, between July 2011 and May 2014, a total of 44 patients who presented for PCNL were prospectively enrolled and randomly divided into 2 groups [complete supine (n=22), and semi supine (n = 22)]. The results in both positions were compared regarding the complexity and outcomes. Stone free rate was considered as a main target of the study. However, it was the first study to focus on overlapping the vertebral density during the access. Results: The two groups were comparable in age, gender, body mass index, and preoperative glomerular filtration rate, hemoglobin and creatinine. The mean operative time was significantly shorter for complete supine versus semi supine (36.68 ± 14.12 min versus 47.50 ± 16.45 min, P = .024). At the angle of 0?, overlapping with the spine occurred in 7 patients (31.8%) in semi supine group and just in 1 patient (4.5%) in complete supine group. Also, overlapping with the edge of bed occurred in 10 cases (45.5%) of complete supine and 1 (4.5%) of semi supine; the differences were statistically significant (P = .023, P = .002, respectively). No significant difference was found between the two groups in terms of stone free rate and complications. Conclusion: Although, we had to convert two cases from semi supine into the complete supine position but we have demonstrated that PCNL in both positions is safe, effective and suitable for the patients. The stone free rate was similar in both groups. But the complete supine position is associated with a significantly shorter postoperative hospital stay and operative time, which may improve ease and safety of PCNL for patients.